The Hippo pathway regulates intestinal stem cell proliferation during Drosophila adult midgut regeneration - Shaw, Rachael L.; Kohlmaier, Alexander; Polesello, Cédric; Veelken, Cornelia; Edgar, Bruce; Tapon, Nicolas (Development, 2010)
Intestinal stem cells (ISCs) in the adult Drosophila midgut proliferate to self-renew and to produce differentiating daughter cells that replace those lost as part of normal gut function. Intestinal stress induces the activation of Upd/Jak/Stat signalling, which promotes intestinal regeneration by inducing rapid stem cell proliferation. We have investigated the role of the Hippo (Hpo) pathway in the Drosophila intestine (midgut). Hpo pathway inactivation in either the ISCs or the differentiated enterocytes induces a phenotype similar to that observed under stress situations, including increased stem cell proliferation and expression of Jak/Stat pathway ligands. Hpo pathway targets are induced by stresses such as bacterial infection, suggesting that the Hpo pathway functions as a sensor of cellular stress in the differentiated cells of the midgut. In addition, Yki, the pro-growth transcription factor target of the Hpo pathway, is required in ISCs to drive the proliferative response to stress. Our results suggest that the Hpo pathway is a mediator of the regenerative response in the Drosophila midgut.